Phage therapy administered noninvasively could be effective in thin tubes subject to episodic flow despite washout: a simulation study - Blanco, Celia; Chen, Irene A (Physical biology, 2019)
Bacteriophages (phages) have been proposed as candidates for the treatment of bacterial infections in light of emerging antibiotic-resistant microorganisms. Bacterial growth within thin tubes is a particular concern, such as in urinary tract infections and colonization of catheters. However, it is not clear whether phage administration to the urinary tract or in catheters could be effective in the context of flow to the outside (i.e. voiding or saline flush). Here, we adapt a previous model of phage infection to a thin tube geometry mimicking the spatial organization of the urinary tract, including bacterial motility and episodic flow during which phages are washed out of the system. We show that density-dependent dynamics permit propagation of the phage infection and that washout has little effect on the timing of bacterial clearance. In addition, instillation of phage at the bottom ~0.1 mm of the tract is effective in our computational model, suggesting that therapeutic phage introduced non-invasively could be efficacious in such situations.